Why Inflation Targeting? - Freedman, Charles (IMF Working Papers; Working Paper, 2009)
This is the second chapter of a forthcoming monograph entitled "On Implementing Full-Fledged Inflation-Targeting Regimes: Saying What You Do and Doing What You Say." We begin by discussing the costs of inflation, including their role in generating boom-bust cycles. Following a general discussion of the need for a nominal anchor, we describe a specific type of monetary anchor, the inflation-targeting regime, and its two key intellectual roots-the absence of long-run trade-offs and the time-inconsistency problem. We conclude by providing a brief introduction to the way in which inflation targeting works.